Spiritualitas untuk Modernitas: Analisis Komparatif Tasawuf Hamka dan Hermeneutika Etis Fazlur Rahman - Maghribi, Hamdan; Hidayah, Alfina; Wahyudi, Muhammad (Spiritualita, 2025)
This article aims to conduct a comparative analysis of the concept of spirituality offered by two prominent modernist Muslim thinkers of the 20th century, Haji Abdul Malik Karim Amrullah (HAMKA) from Indonesia and Fazlur Rahman from Pakistan, as their intellectual response to the challenges of modernity that threaten the relevance of traditional Islamic spirituality. Using in-depth textual analysis and conceptual comparison methods, this study critically examines the main works of both figures, focusing on HAMKA’s Tasauf Moderen and Fazlur Rahman’s ideas on Qur’anic hermeneutics. The study results show that although both share the goal of revitalizing Islamic spirituality to make it functional and relevant, they take fundamentally different approaches. HAMKA undertakes a reform of Sufism from within the tradition, centred on moral education (akhlak) and pastoral care for a mass audience. In contrast, Fazlur Rahman undertakes a radical methodological reconstruction that makes Qur’anic ethics, explored through double movement hermeneutics, the foundation of spirituality oriented toward taqwa (moral-historical responsibility) and philosophical-critical. The conclusion of this research affirms that both models, HAMKA’s accessible reformist-pastoral approach and Rahman’s methodologically robust reconstructive-philosophical approach, though different, collectively offer a rich and complementary intellectual and ethical framework. Implicitly, their thoughts provide vital conceptual resources for contemporary Muslim societies in navigating complex challenges such as religious extremism, consumerist materialism, and secularism, while paving the way for future syntheses of Islamic thought.